2019
DOI: 10.5223/pghn.2019.22.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advance in Very Early Onset Inflammatory Bowel Disease

Abstract: Recent studies on pediatric inflammatory bowel disease (IBD) have revealed that early-onset IBD has distinct phenotypic differences compared with adult-onset IBD. In particular, very early-onset IBD (VEO-IBD) differs in many aspects, including the disease type, location of the lesions, disease behavior, and genetically attributable risks. Several genetic defects that disturb intestinal epithelial barrier function or affect immune function have been noted in these patients from the young age groups. In incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 80 publications
0
45
0
3
Order By: Relevance
“…HLH is a life-threatening condition characterized by hyperinflammation, in which activated T lymphocytes and macrophages accumulate in organs, and produce and induce massive production of proinflammatory cytokines, particularly IFNγ 14 , resulting in tissue damage and multiorgan failure that typically affects the liver and bone marrow 15 . IBD in XIAP-deficient patients usually presents with very early onset 16 ; however, adult onset has also been described 17 , and is characterized by a complicated course, necessity of extensive surgical procedures and unresponsiveness to standard treatment, including biological treatment. These patients have also significantly increased mortality rate, dying within a few years upon manifestation or diagnosis of IBD 18 .…”
Section: Introductionmentioning
confidence: 99%
“…HLH is a life-threatening condition characterized by hyperinflammation, in which activated T lymphocytes and macrophages accumulate in organs, and produce and induce massive production of proinflammatory cytokines, particularly IFNγ 14 , resulting in tissue damage and multiorgan failure that typically affects the liver and bone marrow 15 . IBD in XIAP-deficient patients usually presents with very early onset 16 ; however, adult onset has also been described 17 , and is characterized by a complicated course, necessity of extensive surgical procedures and unresponsiveness to standard treatment, including biological treatment. These patients have also significantly increased mortality rate, dying within a few years upon manifestation or diagnosis of IBD 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to compare the effects of ustekinumab with those of other biologics because of no direct head-to-head trials [11]. In pediatric cases, the response rates to biologics might be lower than adult ones if monogenic IBD was incorporated into the study population [14]. The major concern is a risk of prolonged biologics therapy for children.…”
Section: Discussionmentioning
confidence: 99%
“…Monogenic or Mendelian disorder-associated IBD (MD-IBD) is a term used to represent IBD caused by genetic mutations [ 11 13 ]. After the first report of IBD caused by the mutations of IL10RA and IL10RB by Glockers et al [ 14 ] in 2009, approximately 60 monogenic IBDs have been reported to date [ 15 16 ]. Evaluating and managing children with VEO-IBD are a challenging field for pediatric gastroenterologists worldwide.…”
Section: Introductionmentioning
confidence: 99%